2018
DOI: 10.1177/0098628318796921
|View full text |Cite
|
Sign up to set email alerts
|

The Presentation of Ethics in Undergraduate Psychology Syllabi

Abstract: To identify where ethics is presented to undergraduate psychology students, this study reviewed a national sample of 706 syllabi for required mandatory psychology courses. The results indicated that 6 syllabi were designated as ethics courses and 65 syllabi did not mention ethics at all. Even though 641 syllabi mentioned ethics, the most frequent listing was under course policies, usually as a standard statement (e.g., academic honesty and plagiarism) required by many institutions. Our recommendation is that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Korn (1984) states there is minimal coverage of research ethics in introductory psychology or social psychology textbooks. Despite APA recommendations that it be integrated into courses throughout the major (APA, 2013), Ruiz and Warchal's (2014: 121) review of scholarly publications on teaching ethics in psychology found 'little evidence to support that ethics is being taught in any systematic fashion', and You, Ruiz, and Warchal (2018) found that ethics is not a focus in undergraduate syllabi. The work of Adair, Lindsay, and Carlopio (1983) and Bachiochi et al (2011) suggests that the class time devoted to ethics varies by instructor and tends to emphasize adherence to the APA code.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Korn (1984) states there is minimal coverage of research ethics in introductory psychology or social psychology textbooks. Despite APA recommendations that it be integrated into courses throughout the major (APA, 2013), Ruiz and Warchal's (2014: 121) review of scholarly publications on teaching ethics in psychology found 'little evidence to support that ethics is being taught in any systematic fashion', and You, Ruiz, and Warchal (2018) found that ethics is not a focus in undergraduate syllabi. The work of Adair, Lindsay, and Carlopio (1983) and Bachiochi et al (2011) suggests that the class time devoted to ethics varies by instructor and tends to emphasize adherence to the APA code.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Learning about research ethics in Introductory Psychology helps students understand their own rights as research participants, as many departments have subject pools that use Introductory Psychology students as a convenience sample (Sieber & Saks, 1989). Nevertheless, undergraduate psychology syllabi typically mention ethics in the context of academic honesty and plagiarism, rather than as a learning objective (You et al, 2018).…”
Section: Teaching Research Ethics In Psychologymentioning
confidence: 99%
“…Similarly, in psychology the recommendation is to incorporate ethics throughout the program and possibly add a stand-alone ethics course as a capstone (APA, 2013;Dunn et al, 2010;Halpern, 2010;Landrum & McCarthy, 2012;You et al, 2018). Such a program was presented by Ruiz and Warchal (2014).…”
Section: Theme 1 -Delivery: Where and Whenmentioning
confidence: 99%
“…Ethics education should be available in all undergraduate psychology courses, as a common thread (APA, 2013;Dunn et al, 2010;Halpern, 2010;Landrum & McCarthy, 2012;You et al, 2018). The British Psychological Society (2015) suggested that the teaching of ethics should be considered as the teaching of any other subject (p. 10).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation